manamesasher
For the following system, use the second equation to make a substitution for y in the first equation.
3x + y = 2
y + 4 = 3x



This Question is Closed

manamesasher
Best Response
You've already chosen the best response.
0
3x+ 3  4x= 2?

RyanL.
Best Response
You've already chosen the best response.
1
solve for y on the second equation

manamesasher
Best Response
You've already chosen the best response.
0
1?

RyanL.
Best Response
You've already chosen the best response.
1
y + 4 = 3x
y + 44 = 3x4
y = 3x4
Plug that into
3x + y = 2
What do you get then?

manamesasher
Best Response
You've already chosen the best response.
0
3x+ 3x 4 = 2?

RyanL.
Best Response
You've already chosen the best response.
1
Yes you are correct. Then solve for x